Comparison of intravenous gamma globulin and a monoclonal anti-Fc receptor antibody as inhibitors of immune clearance in vivo in mice. - Kurlander, R J (1986)
Fc-receptor-mediated clearance and nonspecific phagocytic clearance were assessed after the infusion of monomeric human IgG, heat-aggregated human IgG, and a monoclonal anti-mouse macrophage FcII receptor antibody (2.4G2) into normal mice. Each agent blocked Fc-receptor function in vivo, but 2.4G2 was much more potent per microgram than the other agents. Monomeric IgG in blocking doses did not affect other aspects of immune function. In contrast, aggregated IgG, and to a lesser extent, 2.4G2 reduced serum complement levels. In addition, these agents also caused moderate reductions in nonspecific phagocytic function. Monoclonal anti-mouse macrophage C3bi receptor antibody (Mac-1), another monoclonal antibody which binds to macrophage CR3 receptors without interfering with Fc-receptor function, also reduced serum complement and inhibited nonspecific phagocytic function. Complement depletion alone (produced by infusion of cobra venom factor) could not account for the observed changes in Fc receptor or nonspecific phagocytic function. We conclude that both monomeric IgG and anti-Fc-receptor antibodies can markedly inhibit Fc-receptor function in vivo; however, the pattern of physiologic changes produced by these agents differs.